2017
DOI: 10.1002/anie.201703977
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Photoelectrochemical Reduction of Carbon Dioxide to Formic Acid: A Functionalized Ionic Liquid as an Absorbent and Electrolyte

Abstract: Photoelectrochemical (PEC) reduction of carbon dioxide (CO ) is a potential method for production of fuels and chemicals from a C1 feedstock accumulated in the atmosphere. However, the low solubility of CO in water, and complicated processes associated with capture and conversion, render CO conversion inefficient. A new concept is proposed in which a PEC system is used to capture and convert CO into formic acid. The process is assisted by an ionic liquid (1-aminopropyl-3-methylimidazolium bromide) aqueous solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
62
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(65 citation statements)
references
References 48 publications
1
62
1
Order By: Relevance
“…Interestingly,as the reaction temperature rises from 303 Kto363 K, the partial current density (PCD) of formate improves more than two times with 52.9 mA cm À2 ,despite the decrease in CO 2 solubility. [2,[10][11][12][13] Despite these significant results,t heir kinetics of CO 2 Rconversion into formate is still limited by the low CO 2 concentration in electrolytes.I nr ecent years,s ome research groups reported remarkable improvement in the current density of CO 2 Rt of ormate using gas diffusion electrodes (GDEs) with metal nanoparticles. [1][2][3][4] There are several electrochemical pathways to convert CO 2 into valuable products, [1,5,6] among which formic acid or formate has received particular attention over the past few years because the CO 2 Ri nto formic acid is regarded as as uitable reaction for industrial scale production.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly,as the reaction temperature rises from 303 Kto363 K, the partial current density (PCD) of formate improves more than two times with 52.9 mA cm À2 ,despite the decrease in CO 2 solubility. [2,[10][11][12][13] Despite these significant results,t heir kinetics of CO 2 Rconversion into formate is still limited by the low CO 2 concentration in electrolytes.I nr ecent years,s ome research groups reported remarkable improvement in the current density of CO 2 Rt of ormate using gas diffusion electrodes (GDEs) with metal nanoparticles. [1][2][3][4] There are several electrochemical pathways to convert CO 2 into valuable products, [1,5,6] among which formic acid or formate has received particular attention over the past few years because the CO 2 Ri nto formic acid is regarded as as uitable reaction for industrial scale production.…”
mentioning
confidence: 99%
“…[2,[10][11][12][13] Despite these significant results,t heir kinetics of CO 2 Rconversion into formate is still limited by the low CO 2 concentration in electrolytes.I nr ecent years,s ome research groups reported remarkable improvement in the current density of CO 2 Rt of ormate using gas diffusion electrodes (GDEs) with metal nanoparticles. [2,[10][11][12][13] Despite these significant results,t heir kinetics of CO 2 Rconversion into formate is still limited by the low CO 2 concentration in electrolytes.I nr ecent years,s ome research groups reported remarkable improvement in the current density of CO 2 Rt of ormate using gas diffusion electrodes (GDEs) with metal nanoparticles.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the electrodes and electrolytes are all of great importance in the reduction of CO 2 . In the imine‐based [APMIm]Br IL electrolytes, an [APMIm−CO 2 ] + complex can be generated quickly through a hydrogen bonding interaction between CO 2 and the [APMIm] + cation, and then CO 2 reduction takes place in the photocathode. Initially, the QDs sensitizer absorbs light energy to make the electrons of the VB jump into the CB as active photoelectrons, which can transfer efficiently into the CO 2 reduction reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, this merit has been applied to the PEC CO 2 reduction. The utilization of ionic liquid (i.e., 1-aminopropyl-3-methylimidazolium bromide) significantly promotes the conversion of CO 2 to HCOOH and suppresses the competitive hydrogen evolution [74].…”
Section: Solventmentioning
confidence: 99%